Energy saving technique for cooling dominated academic building: Techno-economic analysis of its application - Gilani, S.I.H. (Elsevier Ltd, 2014)
Adaptive cooling technique has been proposed previously, as an energy efficient strategy for a centralized HVAC system in a tropical environment. It served single or multi zone buildings by considering both the occupancy pattern (occupied and unoccupied periods) and the local weather conditions. This technique demonstrated considerable annual energy saving potential, however, the technical consequence and economic evaluation for its application have not been provided. This paper aims to analyze the technical and economical feasibility of the proposed technique for an academic building in Universiti Teknologi PETRONAS. It showed that a dual-duct dual-fan system was required to maximize technical feasibility of the proposed technique due to huge cooling load gap, during occupied and unoccupied periods. At the end, an economic evaluation by using net present worth (NPW) method and 3 financing scenarios were performed by considering the dual-duct dual-fan system. With an assumption of 10. years service time, NPW value of the proposed technique was RM176,404 and hence, it became evident that the proposed adaptive comfort technique was economically feasible. Â© 2014 Elsevier Ltd.